PERI-URBAN DYNAMIC: CONSIDERATIONS FOR ITS STUDY IN THE CASE OF COSTA RICA - Palacios-Alfaro, Melania (2015)
Peri-urbanization allows reconfiguration of urban and rural dynamics from the interaction of social, economic, political, cultural and environmental flows and processes. These processes are studied in the peri-urban interface from the systemic approach, considering elements of the subsystems involved in the geographic configuration of suburban space as developed in the case study of Palacios, Quesada and Zúñiga (2011). The theoretical-methodological peri-urban processes described in this article illustrate some guidelines for the development of peri-urban investigations. These guidelines consider the changing variables such as land use, employment opportunities and popular perception of basic services, subject to the analysis needs of the researcher and the characteristics of the unit of study.